2011
DOI: 10.1371/journal.pone.0026301
|View full text |Cite
|
Sign up to set email alerts
|

TCRep 3D: An Automated In Silico Approach to Study the Structural Properties of TCR Repertoires

Abstract: TCRep 3D is an automated systematic approach for TCR-peptide-MHC class I structure prediction, based on homology and ab initio modeling. It has been considerably generalized from former studies to be applicable to large repertoires of TCR. First, the location of the complementary determining regions of the target sequences are automatically identified by a sequence alignment strategy against a database of TCR Vα and Vβ chains. A structure-based alignment ensures automated identification of CDR3 loops. The CDR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Molecular structural analysis has revealed that CDR3 mainly recognizes MHC molecules bound to antigenic peptides [20, 21]. Hence, analysis of CDR3 can reveal changes in antigen-stimulated T cells [22, 23], the number of T cell clones, and T cell functioning [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Molecular structural analysis has revealed that CDR3 mainly recognizes MHC molecules bound to antigenic peptides [20, 21]. Hence, analysis of CDR3 can reveal changes in antigen-stimulated T cells [22, 23], the number of T cell clones, and T cell functioning [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…19,20 Therefore, the analysis of a CDR3 profile can reveal changes in the T-cell population stimulated by a specific antigen, 21,22 the amount of a particular T-cell clone and the functional status of T cells. 23,24 T lymphocytes are primarily divided into the CD4 1 and CD8 1 subsets. In peripheral blood from HDs, the TCRs of more than 95% of T cells are composed of alpha and beta chain heterodimers.…”
Section: Discussionmentioning
confidence: 99%
“…500 models of the A6 TCR [23] were built using the homology module of the TCRep 3D approach, as described elsewhere [7]. TCRep 3D makes use of state of the art homology modeling using the Modeller 9v5 software [24], complemented by the use of additional dihedral restraints applied on CDR 1 and CDR2 to drive the loops towards their canonical conformations [25].…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the molecular basis that governs TCR orientation over pMHC is still a considerable challenge, and also an important need in the field of TCRpMHC modeling [7] and, as a direct consequence, in the field of rational TCR design and adoptive cell transfer immunotherapy [8]. This questions has been recurrently discussed, but only a few studies have focused on predicting the actual binding mode of given TCRpMHC structures: the study from Varani et al made use of experimental data obtained from NMR chemical shift mapping to obtain lists of buried residues upon binding [9], while the recent study from Roomp and Domingues pedicted the contacts between the pMHC and the TCR, using a training set of TCRpMHC crystal structures [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation